The Republic of Latvia : 2001 Article IV Consultation Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Latvia. (IMF Staff Country Reports; Country Report, 2002)
This 2001 Article IV Consultation highlights that Latvia has enjoyed a strong economic performance since the last Article IV Consultation in June 2000. Real GDP growth was 6 1\2 percent in 2000 and accelerated to 8 3/4 percent in the first half of 2001; growth has been led primarily by investment. Inflation has remained low at 3 percent in 2000 and 2001. Market sentiment toward Latvia remains favorable, as evidenced by the relatively low yield spread on Latvia's first Eurobond and by the successful issue, in November 2001, of a second Eurobond.